2014
DOI: 10.5951/mathteacmiddscho.20.4.0202
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Integers through Storytelling

Abstract: Students process open-number problems through various ways of thinking. The patterns emerged from the authors' research on student thinking about integers and are connected to teaching tips for the classroom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…These are descriptions of the CMIAS that students used with the integers emerged from my previous study (Wessman-Enzinger & Mooney, 2014. This dissertation study suggests the need for the development and refinement of more robust descriptions of these conceptual models and for the investigation into other possible conceptual models.…”
Section: Rulementioning
confidence: 93%
See 4 more Smart Citations
“…These are descriptions of the CMIAS that students used with the integers emerged from my previous study (Wessman-Enzinger & Mooney, 2014. This dissertation study suggests the need for the development and refinement of more robust descriptions of these conceptual models and for the investigation into other possible conceptual models.…”
Section: Rulementioning
confidence: 93%
“…Other researchers have pointed to other contexts being suitable for helping students grow conceptually with respect to negative integers in rich contexts (Stephan & Akyuz, 2012). Additionally, recent research conducted by this author has shown that students often make sense of negative integers in unconventional and unexpected ways (Wessman-Enzinger & Mooney, 2014). This dissertation study recognizes the complexity of the use of context with learning the integers and it directs attention to investigating the conceptions that students have and need about integers.…”
Section: A Focus On Student Thinkingmentioning
confidence: 94%
See 3 more Smart Citations